2016
DOI: 10.1007/s10549-016-3736-9
|View full text |Cite
|
Sign up to set email alerts
|

Paclitaxel injection concentrate for nanodispersion versus nab-paclitaxel in women with metastatic breast cancer: a multicenter, randomized, comparative phase II/III study

Abstract: Paclitaxel is widely used in the treatment of patients with metastatic breast cancer (MBC). Formulations of paclitaxel contain surfactants and solvents or albumin derived from human blood. The use of co-solvents such as polyoxyethylated castor oil is thought to contribute to toxicity profile and hypersensitivity reactions as well as leaching of plasticizers from polyvinyl chloride bags and infusion sets. Currently, nab-paclitaxel, an albumin-bound paclitaxel in nanometer range continues to be the preferred tax… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
24
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
3
2

Relationship

1
8

Authors

Journals

citations
Cited by 39 publications
(28 citation statements)
references
References 20 publications
0
24
0
Order By: Relevance
“…After observation of the eligibility criteria, 19 primary articles were selected, including 16 articles in English and three articles in Chinese (Figure 1). 5,18,20,21,[24][25][26][27][28][29][30][31][32][33][34][35][36][37][38] These articles comprised a total of 5787 participants and six paclitaxel formulations including solvent-based paclitaxel, Nab-P, Lip-P, PM-P, PPX, and PICN. The regimens and dose characteristics of the included studies are presented in Table 2.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…After observation of the eligibility criteria, 19 primary articles were selected, including 16 articles in English and three articles in Chinese (Figure 1). 5,18,20,21,[24][25][26][27][28][29][30][31][32][33][34][35][36][37][38] These articles comprised a total of 5787 participants and six paclitaxel formulations including solvent-based paclitaxel, Nab-P, Lip-P, PM-P, PPX, and PICN. The regimens and dose characteristics of the included studies are presented in Table 2.…”
Section: Resultsmentioning
confidence: 99%
“…A phase I study showed that the MTD of PICN is 325 mg/m 2 and that its administration did not cause hypersensitivity reactions. 21 Most studies investigating nanoparticle paclitaxel delivery were performed using head-to-head comparative studies to investigate effectiveness; however safety profiles were not considered. The aim of this study was to compare the ADRs of various paclitaxel formulas by collecting and analyzing randomized controlled trial (RCTs).…”
Section: Introductionmentioning
confidence: 99%
“…A total of eight studies [10][11][12][13][14][15][16][17] which fulfilled our criteria were included in this study. We did not found any difference in efficacy of nab-paclitaxel over paclitaxel (12 months progression free survival-RR FE = 0.86, 95%CI= 0.77-0.97, p= 0.02, I 2 = 25.07%; 24 months progression free survival-RR FE = 0.86, 95% CI= 0.64-1.16, p= 0.34, I 2 = 0%; and 3 years survival-RR FE = 1.20, 95%CI= 0.92-1.56, p= 0.16, I 2 = 37.55%) (Figure 1).…”
Section: Resultsmentioning
confidence: 99%
“…We ultimately identified 22 independent studies published between March 2005 and March 2020 [9,10,12,13,16,21,22,23,24,25,26,27,28,29,30,31,32,33,34,35,36,37]. A flow chart representing selection of studies is shown in Figure 1 Table 1.…”
Section: Identification and Characteristics Of Studiesmentioning
confidence: 99%